Sistem Pendukung Keputusan Rating Mitra Pada Badan Pusat Statistik Kabupaten Aceh Barat Menggunakan Metode Simple Additive Weighting (SAW) - Astrianda, Nica; Away, Asmaul Husna; Suryadi, Suryadi (VOCATECH: Vocational Education and Technology Journal, 2024)
AbstractStatistics Indonesia (BPS) is a non-ministerial government responsible for ensuring the availability of data for use by the government and the public. The data collection process at BPS is conducted through various methods, including surveys, which require substantial manpower. Therefore, BPS employs partners for the data collection process. Partners are recruited through the Sobat BPS application; however, there is often no assessment of these partners within the application, making it difficult for BPS to select high-performing partners. This issue allows for the potential re-selection of irresponsible partners. This study successfully designed and implemented an effective decision support system for evaluating BPS partners using the Simple Additive Weighting (SAW) method. The evaluation results show that this system not only provides accurate and objective assessments but also improves the efficiency of the partner selection process. With 100% accuracy in testing, this system can be adopted as a new standard to ensure that selected partners perform well, thereby supporting BPS in carrying out its duties more effectively and responsibly in the future.AbstrakBadan Pusat Statistik (BPS) merupakan lembaga pemerintah nonkementerian yang bertugas menjamin ketersediaan data untuk digunakan oleh pemerintah dan masyarakat. Proses pengumpulan data di BPS dilakukan melalui berbagai metode, termasuk survei, yang membutuhkan tenaga lebih besar. Oleh karena itu, BPS menggunakan jasa mitra untuk proses pendataan. Mitra direkrut melalui aplikasi Sobat BPS, namun seringkali tidak ada penilaian terhadap mitra pada aplikasi tersebut, menyulitkan BPS dalam menyeleksi mitra berkinerja baik. Masalah ini menyebabkan mitra yang tidak bertanggung jawab dapat terpilih Kembali. Penelitian ini merancang "Sistem Pendukung Keputusan Rating Mitra Pada Badan Pusat Statistik Kabupaten Aceh Barat Menggunakan Metode Simple Additive Weighting (SAW)" untuk menyeleksi mitra berkinerja baik atau buruk agar tidak terulang pada pekerjaan selanjutnya. Hasil penelitian menunjukkan bahwa sistem ini menghasilkan keputusan yang akurat, cepat, objektif, dan dapat menjadi standar baru bagi BPS dalam menyeleksi mitra berkinerja baik. Pengujian perhitungan pada sistem sesuai dengan perhitungan manual menggunakan metode SAW menunjukkan akurasi sebesar 100%.